The third harmony : nonviolence and the new story of human nature - Nagler, Michael N. (Berrett-Koehler Publishers, 2020)
"In the capstone to a brilliant career, Michael Nagler argues that nonviolence-not just as a tactic but as a way of being-is the only way to unite deeply divided people and that without it progressive movements will inevitably fail"--